Distribution of Melanin Pigmentation in 33 Organs of Thai Black-Bone Chickens (Gallus gallus domesticus) - Nganvongpanit, Korakot; Kaewkumpai, Piyatida; Kochagul, Varankpicha; Pringproa, Kidsadagon; Punyapornwithaya, Veerasak; Mekchay, Supamit (Animals (Basel), 2020)
The black-bone chicken (Gallus gallus domesticus) is a breed of chicken that is commonly found in Thailand. This breed is known for having a number of black colored organs. Consumers have been notably attracted to the black-bone chicken breed for the characteristic darkness that is observed in many of its organs. However, the degree of darkness in all organs of the black-bone chicken is still in question. Importantly, there have not yet been any published reports on the distribution of melanin pigment in the organs of the black-bone chicken. This research study aims to examine the distribution of the melanin pigment in 33 organs of the Thai black-bone chicken. Ten black-bone chickens (five male, five female) were included in this study. Thirty-two organs including the brain, spinal cord, sciatic nerve, larynx, trachea, syrinx, lungs, heart, pericardium, aorta, brachial vein, kidney, cloaca, oviduct, testis, gastrocnemius muscle, femur, tongue, esophagus, crop, proventriculus, gizzard, duodenum, jejunum, ileum, cecum, pancreas, liver, gall bladder, omentum, abdominal fat, spleen, and skin were examined in this study. Histological sections taken from tissue samples of each of these organs were studied. The findings revealed that the presence of the melanin pigment was not significantly different (p > 0.005) between male and female specimens. Notably, the liver was the only organ in which the melanin pigment had not accumulated. Consequently, there was not a uniform pattern of melanin pigment accumulation throughout the organs of the chickens. The melanin pigment was present in all of the tissue layers of most organs, while the melanin pigment was found in only specific layers of some of the organs. In conclusion, the distribution of melanin pigmentation in the organs of each of the animals in this study was found to be different. However, in some tissue samples, such as those obtained from the liver, no accumulation of the melanin pigment was observed.